On a Northumberland Barrow and its Contents - Bate, Dorothea M A (Proceedings of the Society of Antiquaries of Scotland, 1912)
Excavation of an oval mound close to Trewitt Hall near Rothbury revealed a roughly made central cist containing only a Beaker vessel. The western cist contained charcoal, worked flint, a pottery sherd and a poorly preserved subadult inhumation. The eastern cist contained charcoal and a few fragments of unburnt bone.